Tiktok as a Generation-Z Islamic Religious Learning Media During the Covid-19 Pandemic - Putri, Angelica Maylani; Astutik, Anita Puji (Jurnal Pendidikan Agama Islam, 2021)
Islamic religious education (PAI) is very much needed for the moral and religious development of Generation Z. Today's teenagers prefer to spend their time playing gadgets rather than listening to lectures in a place of worship. So that many content creators innovate to attract the interest of Generation Z by conveying Islamic religious knowledge online through social media. One of the social media that attracts Generation-Z's interest is the TikTok application. This study aims to determine the use of the features of the TikTok application in creating a method of delivering PAI material to Generation-Z during the covid-19 pandemic. The PAI material presented included fiqh, moral creed, Al-Qur'an Hadith, and the history of Islamic culture. This study uses a qualitative approach with virtual ethnographic methods. Data is obtained by researchers through the process of observation and documentation. The data analysis used includes the stages of data reduction, data display, and concluding. The results of the study show that: 1) The use of the TikTok social network as a medium for delivering PAI teaching materials is considered quite effective and brings a lot of new things in the form of experiences, innovations, knowledge, and methods that are different from before. 2) The most interesting and interesting features and methods for Generation Z in learning PAI on the TikTok social network are the feature "Add Text & Add Sound" and the method "Impersonate or Role Play”.